KINERJA UNIT PELAKSANA TEKNIS DAERAH (UPTD) PEMUNGUTAN PAJAK AIR BAWAH TANAH - Sari, Elanda (Jurnal Ilmu Administrasi Negara, 2016)
Performance Regional Technical Implementation Unit (UPTD) Tax Collection of ground water. The purpose of this study was to describe and analyze the performance UPTD District of Bengkalis in tax collection of underground water and the factors that influence it. This research method including qualitative research. The informants are UPTD Subdistrict Head Bengkalis, an employee of the District UPTD Bengkalis, tax payers and tax collectors officer. The technique of collecting data using interview techniques and documentation, while data analysis techniques using qualitative techniques with a descriptive approach. The survey results revealed that the District Bengkalis UPTD performance in tax collection of underground water in the Department of Revenue Bengkalis basically still low. While the factors that affect the performance of the District UPTD Bengkalis factor is still low awareness of the taxpayer in the form of an obligation to pay taxes as dependents. This makes the tax officers overwhelmed the field officers to collect and shortcomings in implementing tax collection.